(untitled) (Journal of Educational Management, 2012)
Critical Issues for Educational Leadership in Ghana, though not a proposal to kick-start a reform in education across Ghana, it does present the reader with some challenges and dilemmas that confront leaders of educational administration in Ghana and to solve problems of education in Ghana. The book of 129 pages comprises nine chapters. Each chapter raises critical issues regarding education which should be of interest to parents, teachers, school administrators, policy makers, researchers and anybody who has a stake in improving the quality of education in Ghana. The critical issues raised by the author begin from the mission and vision of education to include teaching as a profession, the roles of parents, family, and the community. Apart from discussing the roles of each of these socializing agents in contributing to the growth and development of the child as a socially, economically and morally acceptable member of society through the school system, the author provides overview of perspectives and scholarly opinions concerning leadership in education for interrogation. He asserts from the very beginning of the book that for a school, for that matter, education in Ghana to achieve its purpose, there must of necessity be a visionary leadership with missionary zeal who is prepared to remain focus and also ready to bring all stakeholders on board in fulfilling the mandate of producing a future generation in whom the older generation can confidently entrust our societies, institutions, and the country as a whole without trepidation.